Praktik Sewa-Menyewa Pohon Petai dalam Perspektif Al'aadah Muhakkamah - Siti Murtisah; Mulyana Saleh; Mualim (Program Studi Hukum Ekonomi Syariah (Muamalah), 2026)
Renting (ijarah) is an activity involving mutual assistance or cooperation between the lessee and the owner, including objects such as petai trees. This practice has been carried out for generations and is considered profitable, but it often causes harm to one party due to the absence of a written agreement and speculative outcomes. This study aims to examine how the practice of renting petai trees is conducted in Susukan Village and to analyze it from the perspective of al'aadah muhakkamah. The research method used is qualitative with a field research approach, employing semi-structured interviews. Primary data were collected through interviews, while secondary data were obtained from documentation and various literature sources relevant to the study. All data collected were then reduced, presented, and concluded using data analysis techniques. The findings indicate that the practice of renting petai trees in Susukan Village is well-developed and has been passed down for generations. However, this practice does not fully meet the pillars and requirements of a valid ijarah, as it resembles bay’ al-ma’dum (advance sale of unripe crops), which is prohibited in Islam because it contains elements of gharar (uncertainty). From the perspective of the legal maxim al'aadah muhakkamah, this customary practice cannot serve as a legal basis because it contradicts textual provisions (nash) and the principle of fairness in contracts. Therefore, the custom is considered invalid according to Islamic law.